Brazilian transgender children and adolescents: Attributes associated with quality of life - Fernanda Karla Nascimento; Roberta Alvarenga Reis; Alexandre Saadeh; Fran Demétrio; Ivaneide Leal Ataide Rodrigues; Sueli Aparecida Frari Galera; Claudia Benedita dos Santos (Universidade de São Paulo, 2020)
Objective: to describe attributes associated with the Quality of Life of Brazilian transgender children and adolescents according to their own perception. Method: descriptive study conducted with 32 participants between eight and 18 years old, who were either interviewed or participated in focus groups. The statements were transcribed, grouped with the aid of the Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires software, version 0.7 alpha 2 and described according to the definition of Quality of Life by the World Health Organization concerning to the mental, physical, and social dimensions. Results: it was possible to identify the family nucleus as the main social support for transgender children and adolescents. However, the experience of prejudice and discrimination were negative attributes associated with Quality of Life. Conclusion: the statements indicate that lives of transgender children and adolescents are impacted by social, physical, and mental factors due to the stigma and discrimination experienced. It is expected to contribute to the formulation of public policies related to transgender children and adolescents and expand the discussion on the citizens' duties and rights in relation to transsexuality.